PENGARUH PENAMBAHAN ASAM SITRAT TERHADAP KARAKTERISTIK FILM PLASTIK BIODEGRADABLE DARI PATI KULIT PISANG KEPOK (Musa acuminata balbisiana Colla) (Universitas Negeri Semarang, 2016)
Banana peels can be used as raw material for biodegradable plastic film because the banana peels was consists of starch. Starch was derived from banana peels would be rapidly changing color or browning. Browning was prevented by the addition of citric acid during the process of starch extraction from banana peels. The aim of this study was to determine the effect of citric acid on mechanical properties and capabilities degradation of starch biodegradable film made from this starch (film plastik pati kulit pisang – FPKP). FPKP was made with banana peel starch (pati kulit pisang – PKP) as raw materials, with the addition of glycerol as a plasticizer, and both CaCO3 and CMC as filler, whereas the PKP was obtained by simple extraction methods with or without the addition of citric acid. Glycerol concentration was varied from 20% w/w to 60% w/w, while CaCO3 and CMC were added in a fixed amount. The results was showed that the addition of citric acid affects the color of a PKP produced. The addition of citric acid can enhance the tensile strength of FPKP, up to 4,202 MPa for FPKP with CaCO3 filler and 4.032 MPa for FPKP with CMC filler. For biodegrability of FPKP, the affect of citric acid apply vice versa.